Molecular study of genetic diversity in uropathogenic Proteus spp using RAPD-PCR - Talebi, Alireza; Momtaz, Hassan; Tajbakhsh, Elahe (Researcher Bulletin of Medical Sciences, 2025)
Objective: Proteus species are the most important cause of urinary tract infections after Escherichia coli. Due to the increasing prevalence of this pathogen and the emergence of antibiotic-resistant strains, this study aims to investigate the genetic diversity between P. vulgaris and P. mirabilis isolates isolated from patients with UTI. Materials and Methods: 260 samples were collected from October to January 2021 from men and women in different age distributions. P. vulgaris and P. mirabilis species were identified using routine biochemical and microbiology methods. After determining their antibiotic resistance pattern, the genetic relationship of the selected strains was determined using the RAPD-PCR technique. Results: The antibiotic resistance pattern investigation results showed that all the isolated strains were sensitive to nalidixic acid, cephalothin, ciprofloxacin, and nitrofurantoin. In contrast, all the strains had 100% resistance to tetracycline and penicillin. 34 P. vulgaris isolates were classified into two clusters, A and B. Cluster B predominated among P. vulgaris isolates, and the isolates in this cluster had the most similarities. In comparison, cluster A contained just two isolates. Also, 22 isolates of P. mirabilis were placed in 4 clusters (A-D). The most prevalent sizes of DNA banding patterns identified were 300, 400, 600, and 1000 base pairs. Conclusion: These findings revealed the genetic variety of the investigated clinical P. mirabilis and P. vulgaris isolates. RAPD-PCR was shown to be a suitable fingerprinting technology for Proteus spp. which may be employed for epidemiological investigations and infection control measures.